Sobrepeso e obesidade na gravidez: marcadores bioquímicos e resultados maternos e perinatais - Vernini, Joice Monaliza [UNESP] (2013)
Overweight and obesity are associated with increased risks of pregnancy complications and adverse perinatal outcomes, as well as short- and long-term risks for maternal and child health. To assess delivery, maternal and child outcomes in pregnancies associated with overweight and obesity. This descriptive prospective study included 258 pregnant women who started receiving prenatal care at 20 weeks of gestation. Cases of maternallow weight during pregnancy, multiple gestation, and fetal malformation were excluded. According to prepregnancy body mass index (BMI), study participants were allocated into three groups: EUTROPHY- 18.5 < prepregnancy BMI< 24.9 Kgfm2 (n= 65); OVERWEIGHT - 25.0< prepregnancy BMI < 29.9 Kgfm2 (n = 66); and OBESITY- prepregnancy BMI ~ 30.0 Kgfm2 (n = 127). Statistical analyses were performed using the Chi-square test and analysis of variance (ANOVA) followed by the test of Tukey and logistic regression analysis calculating odds ratio and 95%CI (p < 0.05). Most eutrophic women were adolescents (:-;;;19 years) whereas overweight and obesity were mostly observed in women aged ~ 35 years (p < 0.001). Pregestational DM showed a significant association with obesity (15.74%). Weight gain (WG) was lower among women classified as obese (9.56 ± 7.50 Kg). In largest proportion (45.6%) of women with GP < 8 Kg was found in the obesity group, (p < 0,001). Exercising was more frequent in the overweight and obesity groups (p = 0.0100). A greater proportion of obese mothers (13.39%) had large for gestational age babies (p = 0.0209), and highest mean chest perimeter, abdominal perimeter, placental weight, and placental index. Overweight and obesity increased the risk of gestational hypertension, gestational diabetes mellitus, and mild hyperglycemia. The infants born to obese mothers stayed in hospital for a longer time (3.86 ± 3.93) (p = 0.005). Our results confirm adverse outcomes and underscore the importance of identifying and ...